Improving service level performance by Implementing lean six sigma in smes of the gaming peripherals industry in Peru: a case study - Daza Moran, Francisco Javier (2022)
Lean Six Sigma (LSS) is one of the essential and applicable techniques for any organisation in the 21st century, including small and medium-sized enterprises (SMEs), that wish to grow their competitive advantages. The LSS approach’s insights offer an optimal vision for reducing technical gaps and assessing performance indicators. This case study aimed to improve service-level performance in a gaming peripherals SME by incorporating traditional engineering tools into the Define, Measure, Analyse, Improve, and Control (DMAIC) framework, validating its results through a two-month pilot plan, and analysing process improvement via statistical software. The study’s findings revealed that SMEs could effectively control delays in order processing through statistical control planning regardless of financial capabilities.